2021
DOI: 10.3390/pathogens10020102
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cleavage Sites Proteolytically Processed by NS2B-NS3 Protease in Polyprotein of Japanese Encephalitis Virus

Abstract: Understanding the proteolytic processing of polyprotein mediated by NS2B-NS3 protease contributes to the exploration of the mechanisms underlying infection of Japanese encephalitis virus (JEV), a zoonotic flavivirus. In this study, eukaryotic and prokaryotic cell models were employed to identify the cleavage sites mediated by viral NS2B-NS3 protease in JEV polyprotein. Artificial green fluorescent protein (GFP) substrates that contained the predicted cleavage site sequences of JEV polyprotein were expressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Cleavage of artificial GFP substrates was determined by western blot using antibodies specific to GFP and expression of viral proteases were determined by anti-NS3. Here our results demonstrated that GI-SH7 was able to cleave the sites at internal C, NS2A/NS2B, NS2B/NS3, and NS3/NS4A junctions and exhibited the same cleavage pattern as previously reported for SH-GIII [51] , suggesting that viral protease substitution and protein conformation do not interfere with selection of cleavage sites for proteolytic processing and possibly play no role in genotype displacement.…”
Section: Jev Gi and Giii Ns2b(h)/ns3(pro) Proteases Exhibits Identica...supporting
confidence: 85%
“…Cleavage of artificial GFP substrates was determined by western blot using antibodies specific to GFP and expression of viral proteases were determined by anti-NS3. Here our results demonstrated that GI-SH7 was able to cleave the sites at internal C, NS2A/NS2B, NS2B/NS3, and NS3/NS4A junctions and exhibited the same cleavage pattern as previously reported for SH-GIII [51] , suggesting that viral protease substitution and protein conformation do not interfere with selection of cleavage sites for proteolytic processing and possibly play no role in genotype displacement.…”
Section: Jev Gi and Giii Ns2b(h)/ns3(pro) Proteases Exhibits Identica...supporting
confidence: 85%
“…NS2B (H) (hydrophilic domain of NS2B) essentially acts as a cofactor for the protease activity of the NS3 protein. The initial characterization of the cofactor requirement for various flaviviruses has revealed that the minimal essential region for protease activity is positioned in a 40-50 residue central hydrophilic segment of NS2B (amino acid 45 to 95) [32,58,66,67]. NS2B contains a hydrophilic region, the central region of which contains a β-barrel, which folds around the β-barrel of the NS3 protease for its stability [55].…”
Section: Structure and Role Of Ns2b And Ns2b Hydrophilic Domain In Flavivirus Replicationmentioning
confidence: 99%
“…NS2B-NS3 proteases have been involved in carrying out a variety of important phases, e.g., RNA replication (viral), polypeptide cleavage, and the processing and assembly of viral particles [104,105]. The protease activity of the JEV NS2B/NS3 leads to the viral polyprotein cleavage of the capsid (internal), NS2A/NS2B, NS2B/NS3, and NS3/NS4A sites [32]. Moreover, NS2B-NS3 proteases may also play an important role in the immune evasion by the virus [105].…”
Section: Japanese Encephalitis Virus (Jev)mentioning
confidence: 99%
See 1 more Smart Citation
“…These particles that contain RNA, 12 kb of positive-sense genome that encodes a single polyprotein that is cleaved into 10 proteins predominately by the NS2B-3 protease, except for the maturation digestion of prM into pr and a fully mature M. Once the virus particle is uncoated following infection, flavivirus RNA genomes are replicated. Following replication of the RNA genome, the polyprotein is translated, consisting of three structural proteins (capsid (C), precursor membrane/membrane (prM), and envelope (E)) and seven non-structural proteins, designated as: NS1, NS2A, NS2B, NS3, NS4A, NS4B, and NS5 [ 25 , 26 , 27 ] ( Figure 3 ).…”
Section: Introductionmentioning
confidence: 99%